PROGRAM ADIWIYATA DI SMK 2 BUDURAN SEBAGAI UPAYA PENGEMBANGAN ECO-ENTREPRENEURSHIP MENUJU GENERASI MUDA YANG PEDULI DAN BERBUDAYA LINGKUNGAN - Feri Tirtoni (Jurnal Abadimas Adi Buana, 2018)
Adiwiyata School is one of the government programs in the Ministry of Environment that is able to give awareness to all communities in caring for and preserving the environment. Currently students as agents of change must respond positively to their concern for the environment. So that future generations called students are able to take opportunities that can generate rupiah coffers through entrepreneurial activities by utilizing organic and inorganic waste. Organic and inorganic waste can be used as craft materials such as bags, compost, fertilizer, biogas so as to get a high selling value.